Hortiboletus kohistanensis (Boletaceae), a new bolete species from temperate and subalpine oak forests of Pakistan - Naseer, Arooj; Sarwar, Samina; Khalid, Abdul Nasir; Healy, Rosanne; Smith, Matthew E. (Phytotaxa, 2019)
Hortiboletus kohistanensis is described as a new species from the moist temperate and subalpine oak forests of Pakistan after detailed morphological and phylogenetic analyses as well as comparison with related taxa. This oak-associated species is morphologically distinguished from allied taxa by an areolate pileus surface and whitish stipe base. It is also phylogenetically distinct from H. indorubellus, the most closely related species, from India.